Analisis Pelaksanaan Budaya Pati Ea Suku Lewuk Dalam Kehidupan Sosial Ekonomi Masyarakat Dusun Natarita Desa Darat Gunung Kecamatan Talibura - Mada, Markus (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2023)
This study aims to determine the implementation of the Pati Ea Culture of the Lewuk Tribe in Natarita Hamlet and the Socio-Economic Conditions After the Pati Ea Ceremony in Natarita Hamlet, Darat Gunung Village, Talibura District. This research uses descriptive qualitative method. The research subjects were the Lewuk Tribe Traditional Leaders, community leaders who had organized pati ea events and community leaders in Natarita Hamlet who were actively involved in pati ea events. Data collection techniques used are observation, interviews, and documentation. Data analysis techniques in the form of data collection, data reduction, data presentation and drawing conclusions. The results of the study show that pati ea is a traditional ritual performed to honor the spirits who have died and ask for abundant yields in wulan lelen (rainy season) and to give thanks for the harvest in wulan daran (summer). Kula babong (deliberation), Teme Pelang ( soaking rice), Leron pati ( slaughtering animals) and Ekak ( feeding the ancestors). The Socio-Economic Condition of the Dusun Natarita community after the Pati Ea ceremony experienced a decline due to the community's non-compliance with adat.